Effect of interferential current in patients with fibromyalgia: a systematic review - Mayara Tavares da Silva; Fernanda Mendonça Araújo; Mayara Ferreira Araújo; Josimari Melo DeSantana (Universidade de São Paulo, 2018)
ABSTRACT High-intensity and widespread muscle pain is the main complaint of patients with fibromyalgia. Interferential current is a treatment often used in pain relief; however, its effects on these patients are unclear. The objective of this review was to analyze the effects of interferential current therapy on the treatment of patients with fibromyalgia in previously published scientific articles. We searched the following databases: Central, CINAHL, Lilacs, PEDro, Medline (PubMed), SciELO, Science Direct, Scopus and Web of Science on November 2016. We included only controlled clinical trials and had no restrictions for language and date of publication. We used the Cochrane Collaboration's tool to assess the risk of bias of the articles. We found a total of 415 articles, however, only four of them were selected for analysis. Three of these studies were excluded because they were not controlled clinical trials. Thus, only one study was analyzed for this review. According to the study the combination of ultrasound and interferential current improved pain relief and the sleep quality of patients with fibromyalgia. However, the study presented a high risk of bias, being impossible to verify the isolated effect of the interferential current in those patients. Randomized controlled studies on the use of interferential current in patients with fibromyalgia are lacking on literature. The results of this review evidence the importance of developing future studies with adequate methodological design and using only interferential current therapy to improve the use of this therapy for these patients in this clinical setting.